A comparative socio-economic analysis of water storage schemes in Sub-Saharan Africa - Xenarios, Stefanos; Eguavoen, I.; McCartney, Matthew P. (2012)
The recent interest of international funding organizations for financing water storage schemes in Sub-Saharan Africa as a response to anticipated climate change has revived the debate on more appropriate methodologies for welfare assessments. Increasingly, water storage construction is moving away from single objectives like simple irrigation or hydropower production to multiple purpose systems. The inclusion of other socially and environmental related aspects like poverty alleviation and sustenance of minimum ecological services becomes a highly demanding objective for most of the donors. The multi-objective purpose of water storage questions in turn impacts the scaling of a storage scheme as well as the effectiveness of larger versus smaller technical options. The prevailing monetary assessments of direct costs and benefits appear inefficient to capture the diversity of multi-objective targets and the scaling issue by often indicating sub-optimal solutions. The current study proposes an alternative methodological approach based on an outranking methodology equipped with a set of preference conditions and weighting indices. Though based on the underlying principle of economic efficiency, the approach avoids some crucial weaknesses of the mainstream analysis by giving higher attention to a wider range of criteria. The method was tested in six case studies in Ethiopia and Ghana where representative small and large water storage types of Sub-Saharan Africa (small dams, large dams, wells, river diversion, ponds and soil moisture) were assessed in comparison to each other and then evaluated with the help of ethnographic findings.